Bupropion for depression in schizophrenia: a case report - Englisch, Susanne Angelika; Eßer, Andrea; Zink, Mathias (Pharmacopsychiatry, 2010)
Major depressive episodes (MDEs) are common in the course of schizophrenia, and antidepressant agents are frequently administered. Bupropion, a dual dopamine/norepinephrine reuptake inhibitor, primarily addresses catecholamine neurotransmission which is of pivotal importance in mood regulation. While bupropion proved to be efficient and safe in the treatment of nicotine dependency in schizophrenic patients and as an antidepressant agent did not show an increased psychotogenic risk compared with other common antidepressants, there still have been reports on bupropion-associated psychotic episodes which are held liable for the fact that bupropion is only reluctantly applied in schizophrenia. Here, we describe a schizophrenic patient whose post-psychotic depression was successfully treated with bupropion without worsening the psychotic syndrome.